Chinese research perspectives on society. - Xueyi, Lu; Peilin, Li; Guangjin, Chen; Wei, Li; Xinxin, Xu (Chinese Research Perspectives on Society., 2013)
Chinese Research Perspectives on Society (formerly the China Society Yearbook), Volume 1 continues the tradition of presenting the findings of Chinese Academy of Social Sciences' subject research group for analysis and forecast of the Chinese social situation in 2011.